2021
DOI: 10.1590/1809-4422asoc20200071r1vu2021l4ao
|View full text |Cite
|
Sign up to set email alerts
|

Management of agricultural pesticide packaging in the Piauí Cerrado

Abstract: The study aimed to analyze the role of actors in the reverse logistics chain of used pesticide packaging in the Cerrado of Piauí. To that end, interviews were conducted with representatives of chain agents in the four municipalities that most produce soy in Piauí. Representatives of the Receiving Centers of the Agricultural Defense Agency of Piauí, business agriculture and family farming participated in the research. It was found that, despite positive initiatives of packaging receiving center operators, agric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
3
0
3
Order By: Relevance
“…Misma que muestra el resultado al 100% de reclamos evaluados. Asimismo, se complementa la logística inversa como un instrumento de desarrollo económico caracterizado por un conjunto de acciones, procedimientos y medios diseñados para implementar la recolección y devolución de residuos sólidos al sector empresarial de origen para su reciclaje o reutilización en sus propios ciclos de producción para proceder a una eliminación ambientalmente adecuada del material [10].…”
Section: Reclamos De Clientes Cantidad (Mensual)unclassified
“…Misma que muestra el resultado al 100% de reclamos evaluados. Asimismo, se complementa la logística inversa como un instrumento de desarrollo económico caracterizado por un conjunto de acciones, procedimientos y medios diseñados para implementar la recolección y devolución de residuos sólidos al sector empresarial de origen para su reciclaje o reutilización en sus propios ciclos de producción para proceder a una eliminación ambientalmente adecuada del material [10].…”
Section: Reclamos De Clientes Cantidad (Mensual)unclassified
“…The exploratory and descriptive analysis is based on secondary data provided by relevant bodies, with the intent to ascertain farmers' responsibilities within the Campo Limpo System. Initially, it was observed that the Brazilian crop production structure is heterogeneous, even though the expansion of soybean cultivation in the last three decades brought an apparent spatial homogeneity to the Brazilian agricultural landscape (OLIVEIRA; RODRIGUES, , 2020RODRIGUES, , and 2021. To illustrate this issue, data from the 2017 Agricultural Census carried out by the Brazilian Institute of Geography and Statistics (IBGE) is used.…”
Section: Databasesmentioning
confidence: 99%
“…A central criticism of the Campo Limpo System is that its technical support for the correct handling and disposal of EACs is deficient (MARQUES et al, 2019;MELLO;SCAPINI, 2016;NOGUEIRA;DANTAS, 2013;RODRIGUES et al, 2021). Rigorously cleaning containers before delivering them is crucial, since this is a decisive factor both for mitigating EACs environmental impact and for the operational quality of the recycling operation (PICUNO et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uma das principais críticas ao Sistema Campo Limpo se baseia em um suporte técnico deficiente para o manejo e descarte correto das EVAs (MARQUES et al, 2019;MELLO;SCAPINI, 2016;NOGUEIRA;DANTAS, 2013;RODRIGUES et al, 2021). Uma vez que tanto a diminuição do impacto ambiental quanto a qualidade operacional dependem de um rigoroso procedimento de limpeza das embalagens rígidas antes do retorno, a sua disposição final é de suma importância (PICUNO et al, 2020).…”
Section: Introductionunclassified